The TRINITY Study: distribution of systolic blood pressure reductions - Sugimoto DH; Chrysant SG; Melino M; Lee J; Fernandez V; Heyrman R (Dove Medical Press, 2013)
Danny H Sugimoto,1 Steven G Chrysant,2 Michael Melino,3 James Lee,3 Victor Fernandez,3 Reinilde Heyrman41Cedar-Crosse Research Center and Rush Medical College, Chicago, IL, USA; 2Oklahoma Cardiovascular and Hypertension Center and Department of Cardiology, University of Oklahoma College of Medicine, Oklahoma City, OK, USA; 3Department of Clinical Development, Daiichi Sankyo, Inc, Parsippany, NJ, USA; 4Formerly of the Department of Clinical Development, Daiichi Sankyo, Inc, Parsippany, NJ, USABackground: Elevated systolic blood pressure is more difficult to control than elevated diastolic blood pressure. The objective of this prespecified analysis of the Triple Therapy with Olmesartan Medoxomil, Amlodipine, and Hydrochlorothiazide in Hypertensive Patients Study (TRINITY) was to compare the efficacy of olmesartan medoxomil (OM) 40 mg, amlodipine besylate (AML) 10 mg, and hydrochlorothiazide (HCTZ) 25 mg triple-combination treatment with the component dual-combination treatments in reducing elevated seated systolic blood pressure (SeSBP).Methods: The 12-week TRINITY study randomized participants to either one of the three component dual-combination treatments (OM 40 mg/AML 10 mg, OM 40 mg/HCTZ 25 mg, or AML 10 mg/HCTZ 25 mg) or the triple-combination treatment. The primary outcome of this analysis was the categorical distribution of SeSBP reductions at week 12 from baseline with OM 40 mg/AML 10 mg/HCTZ 25 mg versus the dual-combination treatments.Results: SeSBP reductions >50 mmHg were seen in 24.4% of participants receiving triple-combination treatment versus 8.1%–15.8% receiving dual-combination treatment. More participants receiving triple-combination treatment achieved the SeSBP target of <140 mmHg (73.6% versus 51.3%–58.8%; P < 0.001) and the seated blood pressure target of <140/90 mmHg (69.9% versus 41.1%–53.4%; P < 0.001). Prevalence and severity of adverse events were similar in all treatment groups.Conclusion: Treatment with OM 40 mg/AML 10 mg/HCTZ 25 mg was well tolerated and more effective in reducing SeSBP than the dual-combination treatments.Keywords: olmesartan, angiotensin receptors, calcium channel blockers, thiazide diuretics, hypertension, TRINITY